Karte von dem Eylande Terre-Neuve - Bellin, Jacques Nicolas, 1703-1772 ([Leipzig], 1756)
Hand coloured. Prime meridian Paris. Depths indicated by soundings. Two bar scales: French common leagues, and French and English marine leagues. Includes note describing the island as uncharted territory.